Snow tracking and trapping harvest as reliable sources for inferring abundance : a 9-year comparison - Desrochers, André; Kawaguchi, Toshinori; Bastien, Héloïse (Northeastern Naturalist, 2016)
Trapping harvest and snow tracking are frequently used to infer population dynamics, yet there have been few evaluations of these indices. We developed population indices for Martes americana (American Marten), Mustela spp. (weasels), and Tamiasciurus hudsonicus (American Red Squirrel) from 9 years of snow-tracking data in eastern Canada. We employed mean track counts per unit effort as population indices derived from a generalized linear model (GLM) of track counts as a function of year and covariates including forest age. Mean track counts were significantly correlated with American Marten and weasel pelt sales and year effects in GLM were correlated with American Red Squirrel and weasel pelt sales. The results of both methods are in agreement; therefore they are likely valid sources to infer population dynamics for these species.